A Juridical Analysis of Regional Government Authority in the Fulfillment of the Right to Water in South Sumatra Province Based on Law Number 17 of 2019 on Water Resources - Arafat, Yusri; Izomiddin, Izomiddin; Bukhori, K.A. (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2025)
Water is a basic human need whose fulfillment is guaranteed by the constitution as part of human rights. Following the annulment of Law No. 7 of 2004 by the Constitutional Court, the enactment of Law No. 17 of 2019 concerning Water Resources marked the return of the spirit of state control over water to prevent excessive commercialization. However, in South Sumatra Province, the abundance of water resources has not fully guaranteed easy access to clean water for the community, especially with pressure from the industrial and plantation sectors. The main problems analyzed are how the local government's authority is regulated in Law No. 17 of 2019, how it is implemented in South Sumatra, what juridical and institutional constraints are faced, and what the review of Constitutional Law and Fiqh Siyasah is regarding this authority. This study aims to analyze the authority of local governments in fulfilling the right to water in South Sumatra based on the latest legal framework. This research is a juridical-normative legal study enriched with a juridical-empirical approach through a case study in South Sumatra Province. Data were collected through document studies of laws and regulations, court decisions, and related literature. The analysis was conducted using the welfare state theory, the concept of State Control Rights (HMN), and the Fiqh Siyasah perspective to evaluate the effectiveness and fairness in the implementation of regional authority. The results show that Law No. 17 of 2019 has provided a strong mandate to local governments as public trustees in water management. However, its implementation in South Sumatra still faces significant obstacles, including regulatory disharmony, limited institutional capacity, and conflicts of interest with the macro-economic sector. From the Fiqh Siyasah perspective, water management must emphasize the principle of maslahah 'ammah and the protection of life (hif? al-nafs). The recommendations of this study include the need for harmonization of regional regulations, reform of water utility governance (BUMD), and increased public participation in water resource supervision.